1. ¿Cuál es el procedimiento correcto para resolver la siguiente ecuación?
6(x - 4) = -8 (-x + 4)
A 6(x - 4) = -8 (-x + 4)
6x-4-8x + 4
6x - 8x = 4 + 4
-2x = 8
8
2
B 61X - 4) = -8 (-x + 4)
6x - 24 = 8x - 32
6x - 8x = -32 +24
-2x = -2
ရှိ-
x = 4
Á
-2
x = 4
C 6(x - 4) = -8 (-x + 4)
6x - 24 = -8x - 32
6x - 8x = -32 - 24
-2x = -56
-56
X
-2
D 6(x - 4) = -8 (-x + 4)
6x - 24 = -8x - 32
6x - 8x = -32-24
-2x = 56
56
-2
X = 28
X = -28
Respuestas
Respuesta dada por:
5
Respuesta:
B
Explicación paso a paso:
Preguntas similares
hace 3 años
hace 3 años
hace 5 años
hace 5 años
hace 5 años
hace 7 años